Prevalence of occupational injury and determination of safety climate in small scale manufacturing industry: a cross-sectional study - Afidah Abidin; Khamisah Awang Lukman; Helmy Sajali; Syed Sharizman Syed Abdul Rahim; Fredie Robinson; Mohd Rohaizat Hassan; Firdaus Hayati; Mohd Yusof Ibrahim; Mohammad Saffree Jeffree (Elsevier BV, 2021)
Background: Occupational injuries are among the most important workplace issues. This study aims to determine the safety climate and prevalence of occupational injuries in the small-scale manufacturing industry. Methods: A cross-sectional study with ten small scale manufacturers participated accounting for a total of 300 respondents. Data were collected from July to August 2020 using the NOSACQ-50 questionnaire. Results: The prevalence of occupational injury for the past 12 months was at 18%. The most often injured body parts were hands and legs while among the most common injury types were open wound, burns and bleeding. The mean NOSACQ-50 scores for all dimensions are good. The associated factors are working hours per week, and compliance to SOP. There are differences in the mean scores of NOSACQ-50 between injured and non-injured workers across all dimensions. Conclusion: The safety climate among manufacturing industry employees is at a good level, while the prevalence of occupational injury is relatively low.